Learning Strategy Based on Long Term Retention in Islamic elementary school / Strategi Pembelajaran Berbasis Long Term Retention di Madrasah Ibtidaiyah - Tesi Muskania, Ricka; Supena, Asep (STAI Ma'had Aly Al-Hikam Malang, 2021)
This study aims to describe a learning model based on long term memory retention using the SMART learning model for students at the basic education level that is applied by teachers in the Natural Science (IPA) learning process. The method used is descriptive qualitative with case studies. The data source is high grade teachers in elementary schools. The results showed that the SMART learning model is a model with a STEM (Science, Technology, Engineering, Mathematics) approach that integrates religious and artistic values in learning. This model can be used as a reference for a learning model that has a role to strengthen the retention rate of elementary school science material.